The Value of Functional Multislice Computed Tomography in the Diagnosis of Instability of the Cervical Spinal Motion Segments - S. К. Ternovoy; N. S. Serova; A. S. Abramov; T. I. Miskaryan (Вестник рентгенологии и радиологии)
Objective. Instability of the vertebral motion segments is a very urgent problem of medicine, since it has very serious consequences. Today, search for optimal diagnostic methods continues. The authors propose a new diagnostic technique - functional multislice computed tomography (fMSCT). The objective of the study was to investigate the efficiency of the technique versus radiography.Material and methods. The new technique was used to examine 35 patients with a referral diagnosis of cervical spinal instability, who had previously undergone cervical spine radiography in the frontal and lateral projections.Results. Instability of the spinal motion joints in its clinical manifestations is similar to the hypermobility of the cervical spine. According to the results of fMSCT, the occurrence of signs of instability and hypermobility was assessed. When performing fMSCT, compression of the spinal canal was detected in 48.6% of patients, compression of the spinal roots was revealed in 85.7%. Violation of the integrity of the anterior and posterior support complexes was registered in 11.4% and 97.1% of patients, respectively.Conclusion. The developed fMSCT technique allows to accurately assess both the statics and dynamics of the spine and, unlike radiography, to diagnose ventral and dorsal vertebral displacements. The technique is recommended for widespread use in clinical practice.